2016
DOI: 10.4103/0366-6999.178969
|View full text |Cite
|
Sign up to set email alerts
|

Altered Wnt Signaling Pathway in Cognitive Impairment Caused by Chronic Intermittent Hypoxia

Abstract: Background:Cognitive impairment is a severe complication caused by obstructive sleep apnea (OSA). The mechanisms of causation are still unclear. The Wnt/β-catenin signaling pathway is involved in cognition, and abnormalities in it are implicated in neurological disorders. Here, we explored the Wnt/β-catenin signaling pathway abnormalities caused by chronic intermittent hypoxia (CIH), the most characteristic pathophysiological component of OSA.Methods:We divided 32 4-week-old male C57/BL mice into four groups o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 40 publications
(45 reference statements)
2
15
0
Order By: Relevance
“…Sprague-Dawley rats (adult males, weighing 200–250 g) were purchased from the Laboratory Animal Center, Tongji Medical College. The chronic intermittent hypoxic (CIH) rats were placed in a normobaric chamber (Oxycycler modelA84XOV; BioSpherix, Lacona, NY), and then the O 2 level was reduced from the normal level to 8–10% within 120 s and maintained at approximately 8–10% for 120 s. Subsequently, the oxygen concentration was quickly increased to 21% within 50 s and maintained at this level for 300 s. This process was repeated 8 h/day for a total of 6 weeks, consistent with the experimental procedure of our previous study [ 16 ]. The CIH rats were given a dose of AS1842856 (5 mg/kg) or vehicle on days 28 to 42 at random.…”
Section: Methodssupporting
confidence: 66%
“…Sprague-Dawley rats (adult males, weighing 200–250 g) were purchased from the Laboratory Animal Center, Tongji Medical College. The chronic intermittent hypoxic (CIH) rats were placed in a normobaric chamber (Oxycycler modelA84XOV; BioSpherix, Lacona, NY), and then the O 2 level was reduced from the normal level to 8–10% within 120 s and maintained at approximately 8–10% for 120 s. Subsequently, the oxygen concentration was quickly increased to 21% within 50 s and maintained at this level for 300 s. This process was repeated 8 h/day for a total of 6 weeks, consistent with the experimental procedure of our previous study [ 16 ]. The CIH rats were given a dose of AS1842856 (5 mg/kg) or vehicle on days 28 to 42 at random.…”
Section: Methodssupporting
confidence: 66%
“…Increasing evidence from animal studies and human research has indicated a role for the Wnt/β‐catenin pathway in the regulation of cognition in the adult brain . The main biological effect of the canonical Wnt/β‐catenin pathway is to regulate the degradation of β‐catenin through GSK‐3β, and regulating the activity and level of GSK‐3β and β‐catenin has been considered as a potential target for improving cognition .…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 16 17 ] Emerging evidence indicates that, in the healthy population, cognitive impairment is a severe OSA complication. [ 18 ] In PD, OSA may be associated with increased nonmotor symptoms, particularly cognitive dysfunction. [ 19 ] However, considering RBD may relieve hypoxemia in PD patients with OSA, whether this amelioration protects against cognitive decline is unclear.…”
Section: Introductionmentioning
confidence: 99%